Digital Rights Management: Many Technical Controls on Digital Content Distribution Can Create a Surveillance Society - Hoofnagle, Chris Jay (Science and Technology Law Review, 2004)
Digital Rights Management technologies threaten to fundamentally alter the level of privacy protection United States law and tradition currently provide to media consumers. If left unchecked, the development and implementation of DRM could lead to a “surveillance” society. This essay proposes eight policy principles to extend privacy protection to the distribution of digital media.